Development of a Website for Solving Mathematical Problems to Enhance Vocational High School Students' Motivation - Nurbaiti, Idhata; Gunawan, Gunawan (Universitas Muhammadiyah Sumatera Utara (UMSU), 2026)
This study aims to enhance mathematics learning outcomes by developing a problem-solving learning website to motivate students on sequences and series material at SMK Ksatrian Purwokerto. The research method employs an RD approach using the ADDIE model and purposive sampling. Samples were drawn from Class XI TKJ 3 as the control group and Class XI TKJ 5 as the experimental group (website). The problem-solving strategy utilized Polya's steps. Hypothesis testing was conducted using an independent t-test to analyze mean differences, with the One-Sample Kolmogorov-Smirnov test for normality as a prerequisite. Results indicate that the data met assumptions of normality and homogeneity, and the implementation of the website-based problem-solving approach significantly improved students' cognitive scores and learning motivation on sequences and series material compared to the control group. Correlation analysis reveals a positive influence between problem-solving ability and learning motivation.